2018
DOI: 10.1055/a-0630-1397
|View full text |Cite
|
Sign up to set email alerts
|

Could Lipid Profile be Used as a Marker of Autonomous Cortisol Secretion in Patients with Adrenal Incidentalomas?

Abstract: Adrenal incidentalomas (AIs) have been associated with an increased risk of metabolic syndrome and dyslipidemia, though evidence regarding the latter is limited. Lipid abnormalities in patients with AIs have been associated with subclinical hypercortisolism. The current study aims to test whether lipid profile in patients with AIs predicts "autonomous cortisol secretion" (ACS). Patients with AIs found on either computerized tomography (CT) or magnetic resonance imaging (MRI), were included in a prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In a large-scale study, Al-Daghri et al 56 found that WHR was less significant than other anthropometric measures of obesity regarding the strength of association with VD status. However, the inverse correlation observed between VD levels with waist 49,50,57,58 or hip 51,53,59,60 circumferences in previous studies may result due to subcutaneously visceral adiposity alterations. 39,46,54,61 Similar alterations were also noted in elderly Korean women.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a large-scale study, Al-Daghri et al 56 found that WHR was less significant than other anthropometric measures of obesity regarding the strength of association with VD status. However, the inverse correlation observed between VD levels with waist 49,50,57,58 or hip 51,53,59,60 circumferences in previous studies may result due to subcutaneously visceral adiposity alterations. 39,46,54,61 Similar alterations were also noted in elderly Korean women.…”
Section: Discussionmentioning
confidence: 66%
“…The branching point in the metabolism is 7-cholesterol (7DHC) from which both VD and cholesterol are formed. 52,53 Accordingly, some relevant research hypothesized a linkage between cholesterol, VD, and steroid hormones in some subclinical cases. 45,54 VDD has recently been linked to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional tumors result in endocrine disorders such as Cushing's syndrome, hyperaldosteronism, female virilization, or male feminization. Although functional adrenal incidentalomas were early associated with high LDL-C [235], several later studies found no association with lipoprotein cholesterol changes [236,237].…”
Section: Adrenal and Testicular Cancermentioning
confidence: 99%
“…The potential interference of statins (HMG-CoA inhibitors) in steroidogenesis has been hypothesized since their discovery, but previous studies have been inconclusive about their effect on cortisol production [5][6][7]. Most reported studies focused on the established effects of statins after at least two-week administration; statins are used for their lipid-lowering and other effects in patients with coronary artery disease and diabetes [8,9], and several side effects have been noted [10][11][12][13][14][15]. We designed a small-scale study in a cohort of individuals not taking statins and in mice to test the hypothesis that statins could elicit acute changes in the steroidogenic pathway of the adrenal cortex.…”
Section: Acute Statin Administration Reduces Levels Of Steroid Hormonmentioning
confidence: 99%